The limiting normal cone of a complementarity set in Sobolev spaces. (3rd October 2018) - Harder, Felix; Wachsmuth, Gerd
ABSTRACT: We investigate the limiting normal cone of the complementarity set associated with non-negative functions in the Sobolev space . By using results from homogenization theory, we provide lower estimates for this limiting normal cone. These estimates are unpleasantly large.